Договірна свобода як засада договірного права України - Чубоха, Н.; Chubokha, N. (Східноєвропейський національний університет імені Лесі Українки, 2018)
Стаття присвячена договірній свободі у цивільному праві як основоположній засаді договірного права. Розглянуто зміст зазначеної засади, її співвідношення з іншими принципами цивільного права, зокрема, диспозитивністю. Розкрито значення договірної свободи у розвитку договірного регулювання цивільних відносин. Розширення сфери договірного регулювання цивільних відносин вдосконалить правове регулювання, заповнить наявні у ньому прогалини, позитивно впливатиме на розвиток і приватного права, і відповідних правовідносин. The article is devoted to the issue of Freedom of contract as a judicial concept in civil law which is considered in the article as the fundamental principle of contractual law. The author reveals the content of the above mentioned principle, its relationship with other principles of civil law, namely, the principle of discretion, laying emphasis on the importance of freedom of contract in the development of contractual regulation of civil relations. Contractual regulation, based on the contractual freedom of subjects, is intended to ensure optimal legal regulation of civil relations and is enabled to do it most fully, objectively, taking into account the interests of individuals and society. It is freedom of contract that opens up perspective for the development, identification and realization of private initiatives of subjects of civil legal relations which promote the development of modern contractual relations. Expansion of the sphere of contractual regulation of civil relations will improve legal regulation, fill in the gaps in it, will have a positive effect on the development of both private law and relevant legal relations.
Freedom of Contract as a Basic Principle of Contract Law in Ukraine
Keywords: принципи цивільного права; диспозитивність; свобода договору; договірне регулювання; principles of civil law; discretion; freedom of contract; contractual regulation